A Case of Infertility with PCOD Treated with Non Invasive Homoeopathy (Advancements in Homeopathic Research, 2022)
Background:Infertility is medically defined as –”the inability to conceive after multiple sustained attempts of unprotected intercourse for at least 2years. The most common cause of medically treatable infertility is polycystic ovarian syndrome (PCOS).” Polycystic ovary syndrome (PCOS) affects 8-10 percent of reproductive-aged females, making it the most common state of endocrine dysfunction in women. Patients with PCOS are often treated for the signs and symptoms of the condition without consideration for the underlying syndrome, causing frustration for many affected patients. However these cases present with many complications and found to be incurable in contemporary system and treatment is also very costly; a case of PCOS with infertility treated at Central Research Institute (Homoeopathy), NOIDA, with constitutional homoeopathic medicine is presented. The case was followed up over a period of 1.5 years with marked improvement which is evident from regularity of menstrual cycle, from the USG reports, other biochemical tests and successful delivery of a female child. Methods: A single clinical case of PCOS with secondary infertility in a 24 year married female was treated on the lines of individualized homoeopathic treatment. USG and other hormonal assessments were done to record changes in the condition. Results: The 2year old case of PCOS with secondary infertility in which female improved remarkably with single homoeopathic medicine Pulsatilla and the symptoms of PCOS did not recur in last 2 year with delivery of a female child 1year back. Conclusion: Homoeopathy can take care of chronic problems in an individual, where hormonal treatment is advised. Non- recurrence of complaints since 2 year suggests permanent cure is achievable through individualized homoeopathic treatment
Keywords: Hirsutism; homoeopathy; hyperandrogenism; polycystic ovaries; polycystic ovary syndrome; Secondary infertility